Strategic implementation and high performance work practices: a proposed model for public sector - Muhammad, Ibrahim Garba; Abdullah, Haim Hilman (MAYFEB TECHNOLOGY DEVELOPMENT Toronto, Ontario, Canada, 2016)
In view of the dominance of research on high performance work practices and organizational performance literature in the private sector, this paper developed an integrated conceptual model connecting three theoretical propositions in the public sector. The integrated theories comprise the Resource based view perspective and social exchange theories considering the proposed moderating model of Resource management model as an extension of Resource based view perspective. Based on the theoretical propositions a model was developed and interrelationships among the theories were highlighted to guide future empirical investigation.